2018
DOI: 10.1007/s12024-018-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Chest compression-associated injuries in cardiac arrest patients treated with manual chest compressions versus automated chest compression devices (LUCAS II) – a forensic autopsy-based comparison

Abstract: The aim of this autopsy study was to investigate chest-compression associated injuries to the trunk in out-of-hospital and in-hospital non-traumatic cardiac arrest patients treated with automated external chest compression devices (ACCD; all with LUCAS II devices) versus exclusive manual chest compressions (mCC). In this retrospective single-center study, all forensic autopsies between 2011 and 2017 were included. Injuries following cardiopulmonary resuscitation (CPR) in patients treated with mCC or ACCD were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 39 publications
5
57
0
3
Order By: Relevance
“…It should however, be of some concern that the same measure that ensures safety for the provider, in our study, at least, seems to increase the risk for the patient. As in three other studies, we found a strong association between injuries and duration of chest compression 20,22,26 . This calls for measures to reduce the prehospital duration of chest compression.…”
Section: Injury Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…It should however, be of some concern that the same measure that ensures safety for the provider, in our study, at least, seems to increase the risk for the patient. As in three other studies, we found a strong association between injuries and duration of chest compression 20,22,26 . This calls for measures to reduce the prehospital duration of chest compression.…”
Section: Injury Characteristicssupporting
confidence: 90%
“…There is uniform agreement that external chest compression per se may result in intrathoracic and intraabdominal injuries [15][16][17][18][19][20][21][22][23] . Several studies concerning manual-CPR alone report no association between the duration of chest compression and injuries 7,15,16,24,25 .…”
Section: Injury Characteristicsmentioning
confidence: 99%
“…Mechanical chest compression devices have been shown before to cause more thoracic damages, especially when used over a longer period of time (15) (16) and compared to manual chest compressions (17) (18) . These usually range from lung contusions (19) over sternal and rib fractures (20) to haematothorax and haematopericardium (21) , the latter being especially dangerous and immediately life-threatening independent of the original cause of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Die externe Herzdruckmassage ist stets ein massives stumpfes Thoraxtrauma [34,46]. Es kann jederzeit zu begleitenden parenchymatösen und vaskulären Verletzungen kommen.…”
Section: Reanimationsverletzungenunclassified
“…Reanimationsverletzungen sollten nach Wiedereinsetzen des Spontankreislaufs (ROSC) stets in der Klinik ausgeschlossen werden, z. B. mittels Computertomografie [46].…”
Section: Reanimationsverletzungenunclassified